Syari'ah Card (Kartu Kredit Syariah) Ditinjau dari Maqashid Syari'ah dan Asas Manfaat - Efrita Norman (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2020)
Sharia card is a sharia banking product that is new, so in practice it needs to get special attention to fit the sharia concept. Sharia card issuance is very beneficial for humans, which makes it easier for humans to make payments, and provides security to humans because they do not need to carry a lot of money. Supposedly, the benefits obtained are not just worldly benefits, but there must be benefits that are going to the afterlife. Islamic banking in this era is booming. Also its products, such as Islamic card products (Islamic credit cards). This paper discusses the system and concept of sharia cards with the Al Maqashid Syariah Perspective. We found that the concept of sharia cards is acceptable with the concept of fiqh, but there are many qualifications. One of the qualifications is the priority of consumers, meaning consumers will not be impressive.